PREVALENCE OF BLACK POINT OF WHEAT UNDER RICE-WHEAT ROTATION IN HARYANA - S. S. JAKHAR; AXAY BHUKER; ASHOK KUMAR (The Bioscan, 2019)
Wheat seed samples were collected from seed producers of public and private sectors comprising of five districts of Haryana during April-May, 2016. All the samples (100.00%) were found infected with black point with an average infection of 0.99 per cent. The severity of black point was highest in Sirsa district with average infection of 1.165 per cent followed by Kurukshetra (1.365%) and Fatehabad (1.058%) whereas, it was lowest in Yamunanagar (0.401%) followed by Hisar (0.603%). Kurukshetra district recorded highest range of infection (0.25-5.80%) followed by Sirsa (0.20-2.45%) whereas, it was lowest in Fatehabad (0.05-0.30%). The severity of black point was highest in DBW17 with average infection of 2.91 per cent followed by HD 2851 (2.25%). The highest incidence of black point (0.05-5.80%) was found in variety HD 2851 followed by HD 3086 (1.25- 3.50%). No variety was found resistant to black point; therefore varieties WH 1142, WH 147 and WH 1105 should be included in seed production programme to minimize black point in wheat.